Analisis Potensi Musculoskeletal Disorder Pada Pekerja Unloading Material Galian C di Kawasan Tambang Gunung Merapi - Ibnu Abdul Rosid; Maria Gratiana Dian Jatiningsih; Vigna Shindy Culatta; Dewi Chandra Nur Setyawati (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2022)
Stone is one of the C type materials from the eruption of Merapi volcano which is a commodity for the people around it. The process of transferring the materials to consumers uses a mode of transportation in the form of trucks. There are two types of trucks that be used, it are dump trucks and non-dump trucks. Non-dump trucks, the process of unloading material is used manually technique, using human power. In the unloading process, problems in the form of work postures were found to have the potential to cause musculoskeletal disorders. The method used in this study to analyze the working conditions using RULA. The results of measurements using the RULA method obtained a final score in the process of lifting the material, the maximum score is 7. Meanwhile, in the process of lifting stone material for transfer or unloading, the final score is 7. So it was concluded that the activity process has the potential to affect the health of workers. and further investigation and improvement of work processes are required as soon as possible.